The Relationship Between Teacher Certification and Improving the Quality of Education at Hinai State High School 1 - Ari Anggara; Nurmisda Ramayani (ALACRITY : Journal of Education, 2025)
This study aims to determine the relationship between teacher certification and the quality of education at SMA Negeri 1 Hinai. The research employed a quantitative approach supported by qualitative data through observation, questionnaires, and interviews. The respondents consisted of 30 certified teachers. The analysis results show a significant relationship between teacher certification and the quality of education. The product moment correlation test obtained a value of 0r = 0,822, which is interpreted as very strong, while the t-test revealed 0t_ count (7.632) > 0t_table (2.048). This indicates that the better the implementation of teacher certification, the higher the quality of education achieved. The interview findings support these results: the principal observed that certified teachers are more disciplined, administratively organized, and actively engaged in self-development. Non-certified teachers considered certification beneficial but often constrained by motivation and administrative burdens. Meanwhile, students perceived certified teachers as more structured, interactive, and engaging in teaching, although the utilization of technological facilities remained limited. The study concludes that teacher certification has a significant contribution to improving the quality of education; however, its effectiveness needs to be supported by teachers’ internal motivation, academic supervision, and adequate school facilities.